“Dari Mata Turun ke Hati”: Penggunaan Eyelash Extensions di Kalangan Siswi Sekolah Menengah - Valensia, Putri Aurelia (Emik, 2023)
Being attractive and beautiful has its own charm which will certainly increase self-confidence. For this reason, women try to improve their appearance, one of which is by doing facial treatment to make them look more attractive. One of the current trends is eyelash extensions which are widely used by women. This article deals with this. This research used a qualitative approach, and it was conducted in Makassar, involving ten female Junior and Senior High School students in Makassar. They are between 14 and 18 years old. Data collection was carried out througuh in-depth interview and observation. Beauty is every woman's dream regardless of age. There are various ways to look beautiful. Eyes are the main aspect of beauty because as a saying state: "from the eyes down to the heart". Eye makeup has a significant influence on the overall beauty of one’s face, even though other parts of the face are not touched by decorative cosmetics. Therefore, special attention is given to apply eye makeup, one of which is by using eyelash extensions. Eyelash extensions also have various forms, namely basic lash or natural eye, soft doll, cat eye, perfect long, open eye. The form of eyelash extensions that is popular among young women is the basic lash type because even if someone uses eyelash extensions, the appearance of this type of eyelash is more natural and not excessive. In addition, there are two types of eyelash extensions, namely classic and premium. However, choosing the form and type of eyelash extensions really depends compatibility on the shape of the user's eyes. The reasons why teenage girls use eyelash extensions are: first, because of the influence of people in their immediate environment who have used eyelash extensions; second, social media has a very significant influence on females teenagers' decisions to use eyelash extensions, through which celebrities and influencers inspire them to use eyelash extensions; third, using eyelash extensions enhance one’s self confidence; and fourth, the relatively affordable price of eyelash extensions motivates female teenagers to use them. However, despite the desire to become more beautiful by using eyelash extensions, there is a "price" that must be paid. Using eyelash extensions has an impact on one's eyes and self. If the former causes itching, irritation, and loss of eyelashes; then the latter makes eyelash extensions users addicted.